2021
DOI: 10.1111/trf.16532
|View full text |Cite
|
Sign up to set email alerts
|

Not a crystal ball: Mapping opportunities and threats for the future demand of red blood cells in the Netherlands using a scenario approach

Abstract: Background As Western blood transfusion practices are changing, there is interest and need in anticipating the future demand of blood products and how a blood establishment can actively prepare for various long‐term developments. This article provides an overview of how a scenario approach was used to prioritize key categories of drivers for the future demand of red blood cells and the organizational implications thereof for Sanquin, the Dutch national blood establishment. Study Design and Methods Based on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Using this approach could be an alternate, and more independent (non‐biased) approach to purchasing reports from commercial companies. Other blood establishments could use this work as a starting point and modify it accordingly, even taking it further by assessing the mitigating measures to mitigate the threats and embrace the opportunities, 107 or using traditional scenario methodology and choosing to focus on certain transformational factors to create specific future scenarios. 15 This methodology was used by Sanquin to make recommendations to the Ministry of Health regarding the need for increased plasma collections, which resulted in the opening of the first plasma‐only collection in the Netherlands center in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach could be an alternate, and more independent (non‐biased) approach to purchasing reports from commercial companies. Other blood establishments could use this work as a starting point and modify it accordingly, even taking it further by assessing the mitigating measures to mitigate the threats and embrace the opportunities, 107 or using traditional scenario methodology and choosing to focus on certain transformational factors to create specific future scenarios. 15 This methodology was used by Sanquin to make recommendations to the Ministry of Health regarding the need for increased plasma collections, which resulted in the opening of the first plasma‐only collection in the Netherlands center in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous work, we found that disruptive events (including a global pandemic) are an important theme that would impact blood product demand so that BEs should become more adaptive, flexible, and be open to change. 13 These elements are important in resilience, and the pandemic was the perfect opportunity to study these elements in action through the singular and collective actions of the teams that undertook COVID‐19 activities. Due to the CCP project being one of the first and most spotlighted projects in the organization, 2 it was a unique opportunity to study team improvisation within this group.…”
Section: Introductionmentioning
confidence: 99%